PENGARUH PEMBINAAN DISIPLIN TERHADAP MOTIVASI KERJA STAF ADMINISTRASI PADA INDUSTRI TEKSTIL DI CIMAHI - R. Mohamad Esa Febriansyah; Fadila Nurfauzia; Megah Dewi Anggini (Jurnal Ekonomi dan Manajemen, 2025)
Human resources are a major factor in Indonesia and can be a major factor throughout the world. Indonesia is now one of the countries that has recorded the largest manufacturing growth in the world. The textile industry is one of the strategic sectors that plays an important role in the country's economy. This sector not only contributes greatly to non-oil and gas foreign exchange, but also absorbs labor and meets domestic needs. Regarding this, the company's efforts to reduce the number of indiscipline employees are by setting sanctions for employees in the form of warning letters and salary deductions. However, the phenomenon that occurs is that the sanctions given by the company against deviations committed by these employees cannot create motivation or encouragement in employees to obey the rules and regulations that have been set by the company. The research method used in this study is a quantitative approach. In this study there are 2 variables, namely: Variable X (Independent Variable) is discipline coaching. Variable Y (Dependent Variable) is work motivation. Because the Sig. value is 0.001 <0.05, then H₀ is rejected. This means that there is a significant influence between Discipline Coaching on Work Motivation. Furthermore, the coefficient of determination of 46.2% of the variation in Work Motivation is explained by Discipline Coaching, while 53.8% is influenced by other factors. There is a positive and significant influence between Discipline Development and Work Motivation of administrative staff in the textile industry.